Fundamentals of Physical Science - Beiser Arthur; Krauskopf Konrad B (Mcgraw Hill Book Company, 1971)
Preface, Matter in Motion, Collective Matter, Electricity and Magnetism, The Atom, Atoms in Combination, Basic Chemistry, Chemistry in Action, Materials of the Earth, Basic Geology, The Evolving Earth, The Sun and Its Family, Mathematics Refresher, Glossary, Answers to Odd-Numbered Exercises, Index.